Fundus Autofluorescence Lifetimes and Spectral Features of Soft Drusen and Hyperpigmentation in Age-Related Macular Degeneration - Hammer, Martin (Transl Vis Sci Technol, 2020)
PURPOSE: To investigate the autofluorescence lifetimes as well as spectral characteristics of soft drusen and retinal hyperpigmentation in age-related macular degeneration (AMD). METHODS: Forty-three eyes with nonexudative AMD were included in this study. Fluorescence lifetime imaging ophthalmoscopy (FLIO), which detects autofluorescence decay over time in the short (SSC) and long (LSC) wavelength channel, was performed. The mean autofluorescence lifetime (τ(m)) and the spectral ratio (sr) of autofluorescence emission in the SSC and LSC were recorded and analyzed. In total, 2760 soft drusen and 265 hyperpigmented areas were identified from color fundus photographs and spectral domain optical coherence tomography (SD-OCT) images and superimposed onto their respective AF images. τ(m) and sr of these lesions were compared with fundus areas without drusen. For clearly hyperfluorescent drusen, the local differences compared to fundus areas without drusen were determined for lifetimes and sr. RESULTS: Hyperpigmentation showed significantly longer τ(m) (SSC: 341 ± 81 vs. 289 ± 70 ps, P < 0.001; LSC: 406 ± 42 vs. 343 ± 42 ps, P < 0.001) and higher sr (0.621 ± 0.077 vs. 0.539 ± 0.083, P < 0.001) compared to fundus areas without hyperpigmentation or drusen. No significant difference in τ(m) was found between soft drusen and fundus areas without drusen. However, the sr was significantly higher in soft drusen (0.555 ± 0.077 vs. 0.539 ± 0.081, P < 0.0005). Hyperfluorescent drusen showed longer τ(m) than surrounding fundus areas without drusen (SSC: 18 ± 42 ps, P = 0.074; LSC: 16 ± 29 ps, P = 0.020). CONCLUSIONS: FLIO can quantitatively characterize the autofluorescence of the fundus, drusen, and hyperpigmentation in AMD. TRANSLATIONAL RELEVANCE: The experimental FLIO technique was applied in a clinical investigation. As FLIO yields information on molecular changes in AMD, it might support future diagnostics.